Pengaruh Kualitas Pelayanan Kesehatan Terhadap Kepuasan Pasien Pengguna Badan Penyelenggara Jaminan Sosial Di Rumah Sakit Anugrah Kabupaten Sidrap - Aswan Yones, Muh.; Tajuddin, Sapri; Hamid, Hariyanti (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2024)
In an effort to meet the needs of the general public and implement legal and regulatory requirements, public service providers carry out all service-related operations under the umbrella of public services. Fair distribution of rights and obligations, requirements, participativeness, openness, accountability and non-discrimination are factors that contribute to good service. At Anugrah Hospital, Sidrap Regency, the aim of this research is to determine the effect of health service quality on patient satisfaction with users of social security administering institutions. The questionnaire served as the primary data source for this quantitative research design. A total of 19 samples from 23 populations were used in this research. The data analysis method uses the SPSS version 21 application for descriptive statistical analysis, validity testing, reliability testing, and basic linear regression analysis. Research findings show that the level of satisfaction of patients using the Social Security Administration is influenced by the quality of health services. Quality is in the "Good" category with a percentage of 78% out of 100%, and regarding patient satisfaction the service is categorized as "Good" with a total percentage of 79% out of 100%. And Hypothesis H0 is accepted.